2016
DOI: 10.1096/fj.201600639r
|View full text |Cite
|
Sign up to set email alerts
|

ORMDL3 expression levels have no influence on the activity of serine palmitoyltransferase

Abstract: ORMDL proteins are believed to be negative regulators of serine palmitoyltransferase (SPT), which catalyzes the first and rate limiting step in sphingolipid (SL) de novo synthesis. Several single-nucleotide polymorphisms (SNPs) that are close to the ORMDL3 locus have been reported to increase ORMDL3 expression and to be associated with an elevated risk for early childhood asthma; however, the direct effect of ORMDL3 expression on SPT activity and its link to asthma remains elusive. In this study, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…Whether this difference asthma-risk alleles are associated with decreased whole-blood sphingolipids. Of note, these results cannot be compared with a study involving a Swiss adult population, in which no associations were found between hydrolytic products of all plasma sphingolipids and rs7216389 genotypes (27). Those analyses cannot distinguish long-chain bases originating from de novo synthesis and were not performed in whole blood.…”
Section: Resultsmentioning
confidence: 80%
“…Whether this difference asthma-risk alleles are associated with decreased whole-blood sphingolipids. Of note, these results cannot be compared with a study involving a Swiss adult population, in which no associations were found between hydrolytic products of all plasma sphingolipids and rs7216389 genotypes (27). Those analyses cannot distinguish long-chain bases originating from de novo synthesis and were not performed in whole blood.…”
Section: Resultsmentioning
confidence: 80%
“…38 ORMDL3 has been proposed as a negative regulator of serine palmitoyltransferase (SPT) enzymes that catalyze the initiation of de novo sphingolipid synthesis, 39 although direct in vivo evidence for ORMDL3 interaction with SPT enzymes has been recently been questioned. 40 Expression levels of ORMDL3 showed no significant changes between controls and IBD patients, regardless of disease severity or disease subtype (UC or CD) (Fig. 1).…”
Section: Discussionmentioning
confidence: 90%
“…ORMDL3 knockout (Ormdl3 2/2 ) mice and ORMDL3 transgenic (Ormdl3 Tg/wt ) mice were previously described. 25 All mice were backcrossed for at least 10 crosses onto a C57BL/6 background. 1-DER mice express an MHC class II-restricted T-cell receptor specific for Der p 1 on their CD4 T cells and were generated, as previously described.…”
Section: Methods Micementioning
confidence: 99%
“…Ormdl3-LacZ reporter mice were generated by inserting a targeting construct into the first intron of Ormdl3 to be able to better address ORMDL3 expression ( Fig 1, A). 25 Although these mice still express some basal Ormdl3 (Fig 1, B), b-galactosidase activity can be used as a readout for Ormdl3 promoter activation.…”
Section: Effect Of Allergen Challenge On Ormdl3 Expression In Asthmamentioning
confidence: 99%
See 1 more Smart Citation